Taking the Occam’s Razor Approach to Hedgehog Lipidation and Its Role in Development - Dominique Manikowski; Philipp Kastl; Kay Grobe (Journal of Developmental Biology, 2018)
All Hedgehog (Hh) proteins signal from producing cells to distant receiving cells despite being synthesized as N-and C-terminally lipidated, membrane-tethered molecules. To explain this paradoxical situation, over the past 15 years, several hypotheses have been postulated that tie directly into this property, such as Hh transport on cellular extensions called cytonemes or on secreted vesicles called lipophorins and exosomes. The alternative situation that tight membrane association merely serves to prevent unregulated Hh solubilization has been addressed by biochemical and structural studies suggesting Hh extraction from the membrane or proteolytic Hh release. While some of these models may act in different organisms, tissues or developmental programs, others may act together to specify Hh short- and long-range signaling in the same tissues. To test and rank these possibilities, we here review major models of Hh release and transport and hypothesize that the (bio)chemical and physical properties of firmly established, homologous, and functionally essential biochemical Hh modifications are adapted to specify and determine interdependent steps of Hh release, transport and signaling, while ruling out other steps. This is also described by the term “congruence”, meaning that the logical combination of biochemical Hh modifications can reveal their true functional implications. This combined approach reveals potential links between models of Hh release and transport that were previously regarded as unrelated, thereby expanding our view of how Hhs can steer development in a simple, yet extremely versatile, manner.